A QoS Model for a RFID Enabled Application with Next-Generation Sensors for Manufacturing Systems - Anna Kang; Jong Hyuk Park; Leonard Barolli; Hwa-Young Jeong (International Journal of Distributed Sensor Networks)
RFID is a new trend in industrial technology such as manufacturing system and product flow management in the supply chain. A successful RFID application can enhance the industrial technology change in organizations and help to manage growth in an increasingly competitive environment. Recently, the RFID sensor tag has also recently received a great deal of attention. In general, the RFID sensor was designed to collect environmental information such as temperature, pressure, humidity, inclination, and acceleration into ordinary RFID tags for internal information processing. In this environment, to apply the RIFID technique to manufacturing systems successfully and efficiently, identifying accurate quality attributes and making a quality model for a RFID enabled application system are necessary. However the research in this area is lacking. This paper focuses on identification of the quality attributes for the RFID application system and making the corresponding model. Each criterion for the quality model was extracted in accordance with ISO/IEC 9126 and the DeLone and McLean model. The proposed quality model also considers the relationship between their criteria.